Aktivisme Digital Warganet Muhammadiyah dalam Menyuarakan Isu Krisis Iklim dan Lingkungan Pada Tagar #Milad111Muhammadiyah - Sofia Hasna (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2025)
In 2023, Indonesia faced a severe climate and environmental crisis. Issues such as the waste crisis, air pollution, and natural disasters called for social movements. Digital activism on social media emerged as a powerful tool to drive change. On its 111th anniversary, Muhammadiyah raised the theme